Bioproduction of Nordihydroguaiaretic and Ellagic Acid from Creosote Bush Leaves (Larrea tridentata) Using Solid-State Fermentation with Aspergillus niger GH1 - Alonso Ascacio-Valdés; Cynthia L. Barrera-Martínez; Juan A. Ascacio-Valdés; Leonardo Sepúlveda (Fermentation)
Creosote bush (Larrea tridentata), a shrub distributed across approximately 19 Mha of arid North American regions, has traditional applications in folk medicine due to the presence of bioactive molecules such as nordihydroguaiaretic acid (NDGA) and ellagic acid (EA). This study investigated the implementation of a solid-state fermentation (SSF) optimization process employing creosote bush leaves as substrate using Aspergillus niger GH1 to improve NDGA and EA extraction. This study was based on previous research by our group that identified key parameters for NDGA production in a related SSF system. Creosote bush is a recognized source of these bioactive compounds, which possess antioxidant and anti-inflammatory properties. Conventional extraction methods often exhibit limitations in efficiency and sustainability. The efficacy of A. niger GH1 in SSF has been previously established with diverse substrates. In this study, A. niger GH1 was employed in an SSF process utilizing creosote bush leaves as a substrate using a Box–Behnken experimental design. The accumulation of NDGA and EA, which were quantified by HPLC-MS, yielded values of 1.20 ± 0.32 mg g−1 for EA and 7.39 ± 0.52 mg g−1 for NDGA. In vitro antioxidant assays (DPPH and ABTS) demonstrated significant antioxidant activity, with inhibition percentages of 55.69% and 84.84%, respectively. These results indicate that A. niger GH1-mediated SSF using Creosote bush leaves is a viable and sustainable strategy for producing these valuable bioactive compounds.